Ibing Pencak Silat Gaya Cimande di Jampangkulon Kabupaten Sukabumi - Muhammad Bangun Prasetyo Widodo; Yuliawan Kasmahidayat (FBS Padang State University, 2023)
Pencak silat can be said as a martial art that has been included in the presentation of performing arts. Because Ibing pencak Silat already contains aesthetic aspects which are distilled into a form of motion for the needs of performing dance. The movement structure of pencak silat has its own technique, broadly speaking it contains attack and defense techniques arranged in such a way as to create a beautiful style. Along with the development of the era of pencak silat, it also follows its development, which now, apart from being a martial art, pencak silat also doubles as a performing art. The purpose of this research was to obtain data and information about the influence of Cimande style pencak silat on the development of Ibing pencak Silat in Jampangkulon. This study uses a qualitative approach with descriptive analysis method. Data collection techniques are carried out by means of observation, interviews, and also documentation. The results of this study show that the Cimande martial arts school is the oldest of several martial arts schools on the island of Java and is known as a large school. Silat Cimande is known as a style of silat that uses and relies more on bare hands, every movement showing movements that explore the limbs of the human body as a gift from God. Cimande's pencak silat can be called one of the parents of the currently circulating pencak styles, and Cimande's movements are also some of the basics of movements that have been developed now. With this research, it is possible to obtain and obtain information about several pagurons in Jampangkulon by studying and discovering the movements resulting from the development of Cimande style pencak silat movements.